The Antar Pakatan Tradition in Sambas Malay Ethnic Weddings (A Study in the Context of Mechanical Solidarity) - Hafiz, Hafiz; Bahari, Yohanes; Ramadhan, Iwan; Zakso, Amrazi; Astari, Zuri (International Journal Ethnic, Racial and Cultural Heritage, 2025)
This study aims to describe Mechanical Solidarity in the Antar Pakatan Tradition in Sambas Malay Ethnic Weddings in Singaraya Village, Semparuk District, Sambas Regency using a qualitative approach with a descriptive method, employing observation, interviews, and documentation for data collection. The findings indicate that collective activities play a crucial role in these weddings, where the local community actively participates in various event stages, such as venue preparation, cooking, arranging dishes, and serving guests, reflecting strong values of family bonds and mutual cooperation (gotong royong). The Antar Pakatan tradition showcases a strong collective awareness, with the community working harmoniously, prioritizing communal interests over individual ones, maintaining unity through cooperation, collective commitment, and a shared focus on the event's success and tradition"™s continuity. Furthermore, this tradition reduces individualism and fosters active participation, where a sense of togetherness and collective responsibility ensures that individuals prioritize community well-being over personal interests, strengthening unity and enhancing the quality of the tradition in uniting the community.